Lift forces on solid spherical particles in wall-bounded flows. (16th January 2020) - Shi, Pengyu; Rzehak, Roland
Highlights: Works concerning lift forces on solid spheres with Rep up 0(1 0  2 ) to are reviewed. Conditions where particles move in stagnant or linear shear flow are considered. Situations where the wall lies in the inner or outer region are distinguished. Non- and torque-free (driven solely by the flow) rotating particles are considered. Improved correlations for wall-lift and shear-lift are proposed. Abstract: The present work is concerned with the lift forces acting on particles immersed in a wall-bounded fluid. Conditions where the particle translates in a fluid at rest and in a linear shear flow are considered. Likewise, non-rotating particles and particles in free rotation driven solely by the flow are considered. Furthermore, situations where the wall lies in the inner region and in the outer region of the flow disturbance produced by the particle are distinguished. The focus is on solid spherical particles at Reynolds numbers up to O 10 2 which are relevant for particulate flows in chemical and minerals engineering. A comprehensive review of existing results from analytical, experimental, and direct numerical simulation studies is given. The available correlations are critically assessed by comparison to data from these studies. Based on the comparison recommendations are given which correlations to use, including some new proposals, and gaps in the data are identified.